Penerapan Metode Hybrid Case Based dalam Diagnosis Penyakit pada Tanaman Karet - Lucky Suriyah Ningsih; Sahat Parulian Sitorus; Rahmadani Pane (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Rubber cultivation utilizing Hevea brasiliensis as the primary source of raw material has established itself as a profitable commercial crop. However, diseases can damage rubber plants and hinder their growth and latex production. To mitigate the resulting losses, it is crucial to develop an efficient expert system for identifying infections in rubber plants. An expert system is a computer program designed to simulate human intelligence in problem-solving and analysis within a specific domain. In this scenario, diseases in rubber plants are identified using an expert system. The Hybrid Case-Based technique, which combines the benefits of Case-Based Reasoning (CBR) method with other methodologies, has proven to be a successful strategy for constructing expert systems. In the Hybrid Case-Based approach, CBR is integrated with other approaches such as Rule-Based Reasoning (RBR). The Hybrid Case-Based technique utilizes information from the existing case base, as well as recognized rules and models, in the context of disease detection in rubber plants. This enables the expert system to diagnose with high accuracy and provide appropriate solutions. The advantages of the Hybrid Case-Based method include its ability to handle complex situations and find optimal solutions. By integrating various approaches, this method overcomes the weaknesses of each individual method. Furthermore, the Hybrid Case-Based approach allows for an overall improvement in the performance of the expert system, resulting in better outcomes in diagnosing diseases in rubber plants. The objective of this research is to utilize the hybrid case-based approach to create an expert system for identifying diseases in rubber plants. It is expected that this research will yield a useful expert system in identifying diseases in rubber plants, which will support farmers in addressing rubber plant health issues. The significance of this research stems from the importance of preserving rubber resources and creating a sustainable rubber economy. When a readily available expert system is capable of accurately identifying infections in rubber plants, farmers can swiftly take necessary steps to halt disease spread and reduce production losses. Additionally, this research can serve as a foundation for developing expert systems in the field of agriculture and other plant diseases. The results of this research indicate that the Hybrid Case-Based method is capable of diagnosing diseases in rubber plants, revealing a low likelihood of White Root Rot disease in the rubber plants with a percentage value of 76%.